History of Ukrainian phonology in training future teachers of language and literature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The history of Ukrainian phonology in training future teachers of language and literature. The article analyzes the formation and development of the Ukrainian phonology, defines the role of knowledge of the history of language for practical work of future teachers of language and literature.
Keywords: phonology; phoneme; history of phonology; linguistic competence; classification of phonemes; phonetic system of the Ukrainian language